2019
DOI: 10.1021/acs.chemmater.8b05112
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Carbene Metal Carbazole Complexes as Photoemitters for Fully Solution-Processed OLEDs

Abstract: Light-emitting carbene-metal amide (CMA) complexes bearing first and second generation carbazole dendron ligands are reported, (Ad L)M(G n), (M = Cu and Au; G n carbazole dendrimer generation, where n = 1 and 2; Ad L = adamantyl-substituted cyclic (alkyl)amino)carbene). The thermal stability of the complexes increases with each dendrimer generation. Cyclic voltammetry indicates that the HOMO/LUMO energy levels are largely unaffected by the size of the dendron, while first reduction and oxidation processes show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 78 publications
(162 reference statements)
4
91
0
Order By: Relevance
“…All gold complexes show a quasi-reversible, carbene ligand-centered reduction process similar to our previous reports. 2,13,29 The peak-to-peak separation DE p varies within a small range of 77-91 mV for gold complexes; this is higher than the expected value of 59 mV for a theoretical reversible one-electron process. The oxazine complex Cu6 shows quasireversible reduction with a peak-to-peak separation DE p of 79 mV, whereas other copper complexes Cu1-Cu3 showed irreversible reduction processes.…”
Section: Synthesis and Structurementioning
confidence: 74%
See 1 more Smart Citation
“…All gold complexes show a quasi-reversible, carbene ligand-centered reduction process similar to our previous reports. 2,13,29 The peak-to-peak separation DE p varies within a small range of 77-91 mV for gold complexes; this is higher than the expected value of 59 mV for a theoretical reversible one-electron process. The oxazine complex Cu6 shows quasireversible reduction with a peak-to-peak separation DE p of 79 mV, whereas other copper complexes Cu1-Cu3 showed irreversible reduction processes.…”
Section: Synthesis and Structurementioning
confidence: 74%
“…Radiative rates exceeding 10 6 s À1 and near unity PLQY values have been realized. [13][14][15] The principle of carbene-metal-amide photoemitters has recently been extended to dendritic systems 29 and to a range of related carbazolate-based CMA systems. [30][31][32] Whereas the studies so far have concentrated on the carbazole ligands, where the amide N-atom is locked into a rigid 5membered ring, we report here a series of CMA complexes carrying amide ligands based on various phenoxazine, phenothiazine, di-and tribenzazepine and sulfone derivatives in which the N-atoms are part of conformationally exible 6-or 7membered rings.…”
Section: Introductionmentioning
confidence: 99%
“…The emission process involved has been subject to a number of theoretical and spectroscopic investigations; [22][23][24] modelling has shown that upon rotation about the metal-N σ-bond, the ΔE(S1-T1) energy gap decreases and at high twist angles may approach zero. 13, [21][22][23][24] Here we report the synthesis of new Au-bridged emitters which enable blue host-free OLEDs with EQEs of 17.3% (λem,max = 473 nm), as well as host:guest devices with a peak wavelength of 450 nm and an EQE of up to 20.9%. At practical brightness levels of 100 cd m -2 , we achieve EQE = 17.2% and EQE = 17.8 % for the best host-free and host:guest devices, respectively.…”
mentioning
confidence: 98%
“…19 These complexes are soluble in most organic solvents and sufficiently thermally stable to enable the fabrication of OLED devices by both solution processing and thermal vapour deposition techniques. 13, [19][20][21] CMAs do not suffer from strong concentration quenching in the solid state, attributed to the lack of close metal-metal contacts, enabling the realization of host-free green devices with an external quantum efficiency (EQE) of 23.1%. 20 Due to the linear two-coordinate geometry, CMAs are conformationally flexible, with a low barrier for rotation about the metal-N σ-bond.…”
mentioning
confidence: 99%
See 1 more Smart Citation